Metformin use is associated with a reduced risk of cognitive impairment in adults with diabetes mellitus: A systematic review and meta-analysis - Zhang, Jia-Hao; Zhang, Xin-Yang; Sun, Yan-Qiu; Lv, Ren-Hua; Chen, Mei; Li, Meng (Frontiers in Neuroscience, 2022)
Abstract Objective: Controversy exists with regard to the impact of metformin, which is associated to prevent or promote the incidence of cognitive dysfunction. Consequently, this systematic review and meta-analysis was conducted to identify the effect of metformin therapy on cognitive function in patients with diabetes. Methods: Electronic databases (PubMed, EMBASE, PsycINFO, the Cochrane Library and Web of science) were systematically searched by two investigators from the date of inception until March 1, 2022. The study followed PRISMA guidelines. Inclusion criteria were defined according to the PECOS model. Eligible researches investigated the effect on cognitive dysfunction in metformin users compared with non-users in adults with diabetes. Only observational study designs (including cohort, cross-section, case-control) were included. Results: A systematic search identified 1,839 articles, of which 28 (17 cohort, 8 case-control, 3 cross-sectional studies) were included in the meta-analysis. Metformin significantly reduced the occurrence of cognitive impairment in patients with diabetes (unadjusted odds ratio [OR]=0.67, 95%CI 0.61 to 0.73; adjusted odds ratio [AOR]=0.92, 95% CI 0.85 to 0.99). Metformin use also was associated with a decreased risk of dementia (OR=0.64, 95%CI 0.59 to 0.69; AOR=0.90, 95% CI 0.84 to 0.96), while a random-effects meta-analysis indicated no significant effect of metformin on reduced the risk of Alzheimer’s disease (AD) (OR=0.85, 95%CI 0.60 to 1.22; AOR=1.17, 95% CI 0.99 to 1.38). Conclusion: Metformin therapy significantly decreased the occurrence risk of cognitive decline in patients with diabetes mellitus. Moreover, the use of metformin by adults with diabetes for the prevention of dementia rather than AD is supported by the available evidence.